PEMULIAAN KACANG TANAH LOKAL JUMBO TIPE TEGAK ROTE NDAO DENGAN METODE IRRADIASI MULTIGAMMA UNTUK MENDAPATKAN VARIETAS BAKAL UNGGUL - Novinda D. M. O. Malelak; Bertholomeus Pasangka; Christin Mbiliyora (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2023)
The research has done using Multigamma Irradiation Method for genetic engineering on local jumbo peanut plants of the upright type Rote Ndao. This research has done in Oesapa Barat, Kelapa Lima District, Kupang City, East Nusa Tenggara. This study is to test the accuracy of the dose for improvement of local jumbo varieties of upright type peanuts irradiated with standard multigamma and to determine tolerance of irradiated mutant varieties to several environmental physical characteristics that are limited to temperature and also the humidity that are not suitable for local peanut growth conditions. The results showed that the right dose to obtain high produce of varieties is dose 4000. The superior characteristics obtained from a dose of 4000 rads included the fastest growing time, the highest number of pods per tree, the highest number of seeds in one pod, the highest protein content, the highest fat content, and the highest mass per 150 seeds. Humidity and temperature of the soil and air in the area planted with Rote Ndao jumbo local peanuts are tolerant of several environmental physical characteristics.